Since the variables (with or without exponents) are not altered in any way, take the coefficients and work with them. Make sure that the variables have matching exponents if you plan on working with them.
9-2=7 therefore 7x^2; -x - x = -2x; -1 -(-3) = -1 + 3 =2
7x^2 - 2x + 2
2006-12-28 08:36:48
·
answer #1
·
answered by icehoundxx 6
·
2⤊
0⤋
First: rewrite this expression in parenthesis in order to distribute the negative sign correctly:
(9x^2 - x - 1) - (2x^2 + x - 3)
9x^2 - x - 1 - 2x^2 - x + 3
Second: combine "like" terms:
9x^2 - 2x^2 - x - x - 1 + 3
7x^2 - 2x + 2
2006-12-28 11:46:28
·
answer #2
·
answered by ♪♥Annie♥♪ 6
·
0⤊
0⤋
(9x^2 - x - 1) - (2x^2 + x - 3) =
9x^2 - x - 1 - 2x^2 - x + 3) =
7x^2 - 2x + 3
And a happy new year!
2006-12-28 08:30:23
·
answer #3
·
answered by Jacaré 2
·
1⤊
0⤋
(9x^2 - x -1) - (2x^2 + x - 3)
=9x^2 - x -1 - 2x^2 - x + 3
= 7x^2 - 2x +2
2006-12-28 08:32:05
·
answer #4
·
answered by mandeep 3
·
2⤊
0⤋
You can only take away like terms so it becomes,
9x^2 - x - 1 - 2x^2 - x + 3
7x^2 - 2x + 2
I think
2006-12-28 08:27:24
·
answer #5
·
answered by Anonymous
·
1⤊
0⤋
(9x^2 - x -1)-( 2x^2 + x - 3)
9x^2-2x^2=7x^2
-x-x=-2x
-1-(-3)=2
7x^2-2x+2
2006-12-28 14:37:05
·
answer #6
·
answered by yupchagee 7
·
0⤊
0⤋
(9x² - x -1) - (2x² + x - 3) =
9x² -x -1 -2x² -x + 3 =
7x² -2x +2
The answer is 7x² - 2x + 2.
<>><
2006-12-28 08:37:50
·
answer #7
·
answered by aeiou 7
·
2⤊
0⤋
9x^2-x-1-(2x^2+x-3)=
9x^2-x-1-2x^2-x+3=
7x^2-2x+2
2006-12-28 09:25:03
·
answer #8
·
answered by Anonymous
·
1⤊
0⤋